Faktor Psikologis dan Pengaruhnya Terhadap Keberhasilan Pembentukan Karakter Mahasiswa di STAPIN Majalengka - Markus Kusni (Sekolah Tinggi Alkitab Penyebaran Injil Majalengka, 2022)
Abstract: STAPIN Majalengka as one of the providers of religious education in Indonesia with a dormitory living system. Through boarding life, it is hoped that a process of character formation and development will occur. Because the purpose of education in addition to producing graduates who excel in academic matters is also required to have superior character. But in boarding life it is not easy to live because this is influenced by several factors. For this reason, this study aims to find out how much psychological factors affect the success of education and character building and character development through boarding life at STAPIN Majalengka. This study uses quantitative methods through field observations by distributing questionnaires to obtain data. The collected data is then processed using SPSS 25